Analisa Citra Penggunaan Media Sosial (Whatsapp dan Line) Sebagai Sarana Komunikasi Kegiatan Gereja yang Efektif [An Analysis of the Image of Social Media Usage (Whatsapp and LINE) as the Means of Communication for Effective Church Activities] - Gandadinata Thamrin (Universitas Pelita Harapan, 2021)
The purpose of this study was to determine whether Whatsapp and Line social media have an effect as a means of communication for church activities where the study used 613 Christian student respondents at Pelita Harapan University, Karawaci using the Image Analysis Method with a familiarity scale and a favorability scale where the initial test of validity and reliability with SPSS and the result is that the use of social media in the church is significant and this research can be used as input for church leaders such as pastors and church members.